Efektifitas Pemanfaatan Sumur Resapan Untuk Mereduksi Limpasan Permukaan - Elsa Rina S; Bambang Sujatmoko; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The amount of runoff in Pekanbaru City makes the function of drainage as a reservoir of excess water cannot function optimally. One of those affected is Vila Tani Housing. The purpose of this study was to compare the effect of form and percentage of use of infiltration wells on the effectiveness of infiltration wells in reducing runoff. The study was conducted with hydrological analysis and infiltration testing. Mathematical calculations were performed to determine flood discharge, concentration time, discharge after the use of infiltration wells, as well as effectiveness for each form of infiltration wells. Flood discharge is obtained at 0.0221 m3 / sec. Forms of infiltration wells that have the greatest effectiveness are wells that are high in water in infiltration wells with the high absorption capacity of wells and the soil surface around infiltration wells that are not water resistant can reduce flood discharge by 53.885% to 0.0102 m3 / sec.Keywords : Runoff, infiltration well, drainage, concentration time